2019
DOI: 10.1089/thy.2018.0549
|View full text |Cite
|
Sign up to set email alerts
|

A Thyroid Hormone-Independent Molecular Fingerprint of 3,5-Diiodothyronine Suggests a Strong Relationship with Coffee Metabolism in Humans

Abstract: Background: In numerous studies based predominantly on rodent models, administration of 3,5-diiodo-L-thyronine (3,5-T2), a metabolite of the thyroid hormones (TH) thyroxine (T4) and triiodo-L-thyronine (T3), was reported to cause beneficial health effects, including reversal of steatohepatosis and prevention of insulin resistance, in most instances without adverse thyrotoxic side effects. However, the empirical evidence concerning the physiological relevance of endogenously produced 3,5-T2 in humans is compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…Of special interest was, similar to the previous studies, the lack of a clear association with serum T4 and/or T3 concentrations (44,45). In a follow-up study of the same cohort, 3,5-T2 serum concentrations were analyzed with respect to urine metabolites analyzed by 1 H-NMR spectroscopy (45)(46)(47)(48). Again, very few individuals had remarkably elevated 3,5-T2 serum concentrations that might be suggestive of underlying disease, although health status could not be traced back due to the population-based study using anonymized sera.…”
Section: A Chemoluminescence Assay Based On Monoclonal Antibodies Detsupporting
confidence: 63%
See 2 more Smart Citations
“…Of special interest was, similar to the previous studies, the lack of a clear association with serum T4 and/or T3 concentrations (44,45). In a follow-up study of the same cohort, 3,5-T2 serum concentrations were analyzed with respect to urine metabolites analyzed by 1 H-NMR spectroscopy (45)(46)(47)(48). Again, very few individuals had remarkably elevated 3,5-T2 serum concentrations that might be suggestive of underlying disease, although health status could not be traced back due to the population-based study using anonymized sera.…”
Section: A Chemoluminescence Assay Based On Monoclonal Antibodies Detsupporting
confidence: 63%
“…Associations of the 3,5-T2 concentrations with various clinical chemistry parameters were moderate. Of special interest was, similar to the previous studies, the lack of a clear association with serum T4 and/or T3 concentrations (44,45). In a follow-up study of the same cohort, 3,5-T2 serum concentrations were analyzed with respect to urine metabolites analyzed by 1 H-NMR spectroscopy (45)(46)(47)(48).…”
Section: A Chemoluminescence Assay Based On Monoclonal Antibodies Detmentioning
confidence: 70%
See 1 more Smart Citation
“…A detailed description of all applied measurement techniques is given in the Supplemental Information. Briefly, four different approaches were combined: 1) non-targeted MS-based profiling of plasma and urine samples as reported previously [27] 2) targeted MS-based profiling of plasma samples using the AbsoluteIDQ p180 Kit (BIOCRATES LifeSciences AG, Innsbruck, Austria) 3) NMR-based profiling of urine samples as reported previously [28] and 4) NMRbased profiling of plasma samples to derive lipoprotein particles.…”
Section: Metabolome Analysesmentioning
confidence: 99%
“…In humans, a few studies have confirmed that the administration of 3,5-T2 can increase the resting metabolic rate, also reducing adiposity and body weight without side effects [250]. Interestingly, through molecular fingerprinting experiments, a strong positive association has been found between the 3,5-T2 levels in the human serum and compounds related to coffee consumption [326]. Taken together, all these finding are encouraging and provide evidence that 3,5-T2 might become a therapeutic agent of utmost importance.…”
Section: The Ins and Outs Of 35-t2 Researchmentioning
confidence: 99%